Remembering exhibitions online: microsites and catalogues raisonnés - Greenberg, Reesa (2021)
In this essay, I discuss two online manifestations of exhibition reprises as memory devices: the microsite and the online catalogue raisonné. For the most part, as currently conceived, these two online forms of remembering exhibitions embody two very different mentalities. Microsites habitually are generated at the time of an exhibition and are born digital; catalogue raisonnés are generated much later and often rely on analogue precedents for design. In addition to promoting the digitally conceived catalogue raisonné, I urge the dual strategy of maintaining active links to historic microsites and the retroactive creation of new ones as vehicles for rewriting the exhibition history canon. My primary examples are drawn from the Centre Georges Pompidou.